Perceptions towards green image of trendy coffee cafés and intention to re-patronage: the mediating role of customer citizenship behavior. Issue 2 (23rd August 2021) - Le, Andrea; Tan, Kim-Lim; Yong, Siew-Siew; Soonsap, Pichsinee; Lipa, Caple Jun; Ting, Hiram
Abstract : Purpose: Drawing upon the stimulus–organism–response (S-O-R) model, the purpose of this study is to examine how perceptions of young customers towards the green image of trendy coffee cafés affect their environmental and product attitudes, and subsequently their citizenship behaviour as well as intention to re-patronage. The mediating effect of customer citizenship behaviour (CCB) is also assessed. Design/methodology/approach: The instrument was developed by adapting measurement from the past studies. Using the purposive sampling technique, data were collected online from 207 young customers in Malaysia who frequented the cafés. Partial least squares structural equation modelling (PLS-SEM) was used to perform path modelling and mediation analyses. Findings: The findings show that green image stimulates both customers' environmental attitude and product attitude. Although product attitude is found to have a dominant effect on CCB, the impact of environmental attitude on CCB and re-patronage intention is worth noting. Moreover, advocacy and tolerance significantly mediate the relationship between product attitude and re-patronage intention. Originality/value: This study advances the consumer behaviour literature by determining the influence of green image on two forms of attitudes as well as the mediating role of the multi-dimensional CCB between attitudes and intention to re-patronage trendy coffee cafés among young customers. While the findings confirm the importance of product attitude and the relevance of advocacy and tolerance in relation to re-patronage, the study also highlights the growing awareness of green image among young customers and its implications on knowledge and practice.